Multigram Synthesis of C4/C5 3,3-Difluorocyclobutyl-Substituted Building Blocks - Melnykov, Kostiantyn P.; Granat, Dmitriy S.; Volochnyuk, Dmitriy M.; Ryabukhin, Sergey V.; Grygorenko, Oleksandr O. (Synthesis, 2018)
An approach for the multigram synthesis of 3,3-difluorocyclobutyl-substituted building blocks (including carboxylic acid, amines, alcohols, azide, trifluoroborate ketone) is described. It is shown that, in most cases, ethyl 3,3-difluorocyclobutanecarboxylate is a convenient common synthetic intermediate to obtain the target derivatives. For preparation of 3,3-difluorocyclobutanol or -cyclobutanone, an alternative pathway via reaction of dichloroketene and tert-butyl or benzyl vinyl ether should be applied.
Keywords: cycloalkanes; organofluorine compounds; fluorination; conformational restriction; lead-oriented synthesis